The identification of CCL18 as biomarker of disease activity in localized scleroderma. (July 2019) - Mertens, J.S.; de Jong, E.M.G.J.; van den Hoogen, L.L.; Wienke, J.; Thurlings, R.M.; Seyger, M.M.B.; Hoppenreijs, E.P.A.H.; Wijngaarde, C.A.; van Vlijmen-Willems, I.M.J.J.; van den Bogaard, E.; Giovannone, B.; van Wijk, F.; et al.
Abstract: Background: Localized Scleroderma (LoS) encompasses a group of idiopathic skin conditions characterized by (sub)cutaneous inflammation and subsequent development of fibrosis. Currently, lack of accurate tools enabling disease activity assessment leads to suboptimal treatment approaches. Objective: To investigate serum concentrations of cytokines and chemokines implicated in inflammation and angiogenesis in LoS and explore their potential to be utilized as biomarker of disease activity. Additionally, to investigate the implication of potential biomarkers in disease pathogenesis. Methods: A 39-plex Luminex immuno-assay was performed in serum samples of 74 LoS and 22 Healthy Controls. The relation between a validated clinical measure of disease activity (mLoSSI) and serum analytes was investigated. Additionally, gene and protein expression were investigated in circulating cells and skin biopsies. Results: From the total of 39, 10 analytes (CCL18, CXCL9, CXCL10, CXCL13, TNFRII, Galectin-9, TIE-1, sVCAM, IL-18, CCL19) were elevated in LoS serum. Cluster analysis of serum samples revealed CCL18 as most important analyte to discriminate between active and inactive disease. At individual patient level, CCL18 serum levels correlated strongest with mLoSSI-scores (rs = 0.4604, P < 0.0001) and in longitudinal measures CCL18 concentrations normalised with declining disease activity upon treatment initiation. Additionally, CCL18 was elevated in LoS serum, and not in (juvenile) dermatomyositis or spinal muscular atrophy. Importantly, CCL18 gene and protein expression was increased at the inflammatory border of cutaneous LoS lesions, with normal expression in unaffected skin and circulating immune cells. Conclusion: CCL18 is specific for disease activity in LoS thereby providing relevance as a biomarker for this debilitating disease. Highlights: Localized Scleroderma (LoS) is characterized by (sub)cutaneous inflammation and subsequent development of fibrosis. Currently, lack of accurate tools enabling disease activity assessment leads to suboptimal treatment approaches. In this study, we demonstrate that serum concentration of CCL18 (PARC) is a biomarker for disease activity in LoS patients. In this study, CCL18 gene and protein expression is increased at the inflammatory border of cutaneous LoS lesions. Abstract : Capsule summary: Tools to determine the disease activity in localized scleroderma (LoS) are lacking. Here, we identified CCL18 as promising biomarker to distinguish between LoS patients with active and inactive disease.